2017
DOI: 10.1111/ggi.13020
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences between older and young adult patients with celiac disease

Abstract: The presentation of celiac disease clinically, histologically and by means of laboratory parameters is different in older and young patients. Polyautoimmunity and multiple autoimmune syndrome are more common in older patients compared with younger patients. A biopsy score of Marsh score type, antinuclear antibody positivity, high serum anti-tissue transglutaminase immunoglobulin A level and low hemoglobin level were risk factors for having an autoimmune disease. Geriatr Gerontol Int 2017; 17: 2060-2067.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
2
0
4
Order By: Relevance
“…CD is also highly associated with other autoimmune diseases. 8,[11][12][13][14] In the large patient cohort study by Grode et al 8 , the disease was associated with 31 different autoimmune comorbid diseases. Studies have shown that CD is more common in patients with type 1 Diabetes Mellitus, thyroiditis, and psoriasis because of shared immune-associated pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…CD is also highly associated with other autoimmune diseases. 8,[11][12][13][14] In the large patient cohort study by Grode et al 8 , the disease was associated with 31 different autoimmune comorbid diseases. Studies have shown that CD is more common in patients with type 1 Diabetes Mellitus, thyroiditis, and psoriasis because of shared immune-associated pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A doença autoimune múltipla, definida como a coexistência de 3 ou mais patologias autoimunes num indivíduo, foi significativamente maior nos idosos (47% vs 4%). 30 A tiroidite de Hashimoto, dermatite herpetiforme (DH), psoríase, diabetes mellitus tipo 1 e síndrome de Sjögren são as doenças autoimunes mais frequentemente associadas à DC no idoso, apesar das variações das suas frequências na literatura. 6,30,31 Muitas outras doenças foram também descritas como associadas à DC como doenças autoimunes hepáticas e doença de Graves.…”
Section: Review Articlesunclassified
“…30 A tiroidite de Hashimoto, dermatite herpetiforme (DH), psoríase, diabetes mellitus tipo 1 e síndrome de Sjögren são as doenças autoimunes mais frequentemente associadas à DC no idoso, apesar das variações das suas frequências na literatura. 6,30,31 Muitas outras doenças foram também descritas como associadas à DC como doenças autoimunes hepáticas e doença de Graves. 30,31 No caso da doença autoimune da tiroide a frequência no idoso varia entre 9% e 17%.…”
Section: Review Articlesunclassified
See 2 more Smart Citations